Submicrometer fiber-optic Fabry-Perot interferometer formed by use of the Langmuir-Blodgett technique - Rees, N. D.; James, Stephen W.; Staines, Stephen E.; Tatam, Ralph P.; Ashwell, Geoffrey J. (Optical Society of America, 2001)
The fabrication of an optical cavity at the distal end of an optical fiber has been achieved by Langmuir-Blodgett (LB) deposition of tricosanoic acid. This technique allows nanometer-scale control over the cavity length to a total thickness of ~0.5 Ã Âµm. The cavity has been shown to act interferometrically and, thus, has potential sensing applications
Keywords: Fiber optics; Fabry-Perot; Interferometry